Beyond the mask: a multidisciplinary reflection on palliating patients with COVID-19 receiving continuous positive airway pressure ventilation. (2nd October 2020) - Hough, Amy; Dell, Georgia Daisy; Blaber, Michael; Kavanagh, Diana; Lock, Anna
Abstract: This narrative describes the experiences of an inner city respiratory unit that was transformed to treat COVID-19 patients with continuous positive airway pressure (CPAP) ventilation who were not scheduled for any further escalation in treatment. The high mortality rate and unconventional way of dying led to the creation of local guidance for removing assisted ventilation when the treatment ceased to be effective. We reflect on the specific challenges that caring for these patients holistically has presented and how we have learnt to deliver good palliative care in a unique set of circumstances. We also consider the impact of the pandemic on our team and how the development of a multidisciplinary support system has improved team dynamics and ultimately patient care.